ANALISIS KEBANGKRUTAN UJI Z-SCORE ALTMAN PADA PT AIR ASIA INDONESIA TBK MENGGUNAKAN MODEL ALTMAN Z-SCORE TAHUN 2018-2022 - Azka, Aditya Fadillah; Nabiilah, Nabiilah; Prameswari, Sekar Natasya; Muyassaroh, Muyassaroh (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2024)
This research analyzes the potential bankruptcy of PT Air Asia Indonesia Tbk using the Z-Score model, focusing on critical financial ratios such as working capital, retained earnings, and share capitalization value. The results show that this company is indicated to have the potential for bankruptcy during the 2018-2022 period, with a Z-Score value below the threshold. Factors such as falling stock prices, plane crashes, and lack of retained earnings contribute to financial difficulties. This research highlights the need for managerial changes to address financial challenges and restore company performance. In conclusion, PT Air Asia Indonesia Tbk needs to take effective preventive measures to ensure long-term sustainability and growth.Keywords: Altman Z-Score, Bankruptcy Potential, Company Performance, Financial Management, Financial Ratios